Changes of hydraulic conductivity of silty clayey sand soil under the effects of municipal solid waste leachate - Asadi, Afshin; Kim Huat, Bujang; Moayedi, Hossein; Shariatmadari, Nader; Parsaie, Alireza (Academic Journals, 2011)
Effect of municipal solid waste (MSW) on the hydraulic conductivity of soil is an important factor for designing liner systems. Leachate samples were collected within a landfill and a composting factory leachate lagoon. Soil samples from the bottom of the Esfahan, Iran, landfill were collected. Effects of the leachates on permeability of the soil samples were investigated. The results of study showed that at the highest level of leachate concentration (100%), the soil showed 20% increase in permeability (k) value from compost leachate and 10% reduction in landfill leachates. Compost and landfill leachates had shown contrasting impact on the soil permeability.